Study on Strength Damage Evolution Regulation of Sandstone under Cyclic Erosion. (15th January 2021) - Meng, Zhigang; Cui, Xuebin; Qi, Gan; Shi, Tingting; Ma, Juan
Abstract : Owing to salt erosion, the sandstone of Yungang Grottoes has widespread weathering diseases. The soluble salt develops reciprocating crystallization pressure under the action of dry and wet cycles to diminish the sandstone strength. Finally, several pore-like and powder-like weathering phenomena are formed. To explore the change in sandstone strength during this process, the sandstone of Yungang Grottoes was taken as the research object. Herein, the uniaxial compression test, XRD test, and other methods were employed to study the samples under different salt erosion cycles. As the number of salt damage cycles increased, the phenomenon of sand particles on the sandstone surface gradually amplified. The compressive strength, tensile strength, and elastic modulus of sandstone decreased with the increase in erosion cycles. The curve was divided into two stages, and the macroscopic and microscopic damage equations of sandstone after erosion were established. During the entire damage process, erosion damage served as the basis of load damage and was affected by different cycles, impacting the development process of load damage. Through the establishment of numerical simulation meso-parameter evolution equations, the PFC2D particle flow model was used to conduct uniaxial simulation tests, and the simulation results were close to the macroscopic test results. Using the particle flow simulation test parameters under salt erosion, the development of the distribution of "displacement-force chain-crack" was analyzed under different salt erosion cycles. These results further revealed the meso-fracture damage characteristics of the Yungang Grottoes sandstone under the action of salt damage and provided a theoretical basis and a novel method for the protection of Yungang Grottoes against weathering.